Um triângulo da marca para evitar a branding myopia: contribuição semiótica para um modelo integrado de compreensão da marca - Lencastre, Paulo de; Côrte-Real, Ana (Organicom, 2007)
This article uses the short-sightedness metaphor to explain the more limited vision of the brand, understood to be the sign of identity of a product. As the brand is a sign, it resorts to semiotics, the science of signs, to apply a model that expands the concept of brand to three dimensions: the sign of identity per se; the object to which the sign relates; and the market’s response to the sign.